Business Communication: Strategies and Practices to Achieve Competitive Advantage - Wardani, Surti (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
This article outlines the important role played by business communication strategies in achieving competitive advantage in an increasingly globalized and digital market era. Through a thorough examination of communication theory, business strategies, and real case studies, this research highlights how effective communication can facilitate more efficient internal operations, strengthen relationships with stakeholders, and provide the necessary support in achieving the company's strategic goals. The findings of this research affirm that integration and adaptability in business communication are key to maintaining the existence and growth of companies in an ever-changing and dynamic environment. By understanding and implementing appropriate communication strategies, companies can gain significant competitive advantages, not only in maintaining operational sustainability but also in creating sustainable value for all stakeholders. Therefore, emphasis on developing competence in business communication becomes increasingly urgent for organizations that want to remain relevant and successful in this continuously evolving market